THE USE OF MIND MAPPING TECHNIQUE IN IMPROVING STUDENTS’ WRITING ABILITY IN NARRATIVE TEXT AT GRADE VIII OF MTs DDI KELURAHAN BARU TOLITOLI - Marzuki, Marzuki (Universitas Madako Tolitoli, 2017)
The objective of this research was to identify whether the use of mind mapping was effective to improve students’ skill in writing narrative text. This pre-experimental study used 25 students as a sample. They were grade VIIIC of MTs DDI Kel.Baru. The procedure of this research consisted of pretest, treatment, and posttest. The researcher gave pretest and posttest to know the use of mind mapping technique can improve the students’ writing ability or not. The result of the analysis showed that mind mapping technique contributed greatly to the students in writing narrative text. It can be seen by the difference of the mean score between pre-test and post-test. The mean score of pre-test was 48.60 while in the post-test improved up to 71.00. The data of this research were analyzed by using SPSS Program 16.0.Moreover, the Minimum Mastery Criterion of English lesson was 75 (seventy-five). Then the data of both tests were analyzed by using T-test, and the result showed that the T-test value 11.362 was greater than T-table value 2.064. It can be inferred that mind mapping technique was very effective to improve students’ ability in writing narrative text. Key words: improving, teaching writing, narrative text, mind mapping technique. ABSTRACT